Padrões de diversidade em comunidades de anfíbios e répteis Squamata no mosaico de florestas naturais e manejadas na região do baixo rio Purus, Amazonas, Brasil - Guimarães, Fabiano Waldez Silva (Instituto Nacional de Pesquisas da Amazônia - INPA, 2012)
The objective of this study was to characterize the patterns of diversity in the communities of amphibians and Squamata reptiles that occur in the forest mosaic of the Piagaçu-Purus Reserve in the lower Purus River, Amazonas, Brazil. The study was conducted in five 1km-transects and 60 plots (10*250m) distributed in seasonally flooded varzea forests and nonflooded terra firme forests, using a diversity of technique which enhanced the probability of representing the herpetofauna diversity in tropical forests: active collecting, pitfall traps with drift fence, and double-ended funnel traps with drift fences. We compared the efficiency of this sampling and the techniques utilized were compared among habitats using Abundance-based rarefaction analysis and four different richness estimators (ACE, Chao 1, Jacknife & Bootstrap). The abundance and the number of species per plot were determined in two diurnal and two nocturnal sampling events in each plot. We verified the contribution of the different types of forest landscapes and the secondary forests in the herpetofauna diversity. We evaluated the influence of environmental factors (altitude, spatial autocorrelation, and the regeneration time of the secondary forests) and historical factors (interfluvial regions of the Purus River and connection of the Purus River varzea forests of the forests to the Amazonas-Solimões Basin) on the distribution of the herpetofauna. Interviews were conducted in some of the local riverside communities within the study area to determine incidents of snakebites, and were recorded ecologic aspects (snake diversity, snakes local names, and attack behavior) and epidemiologic aspects (incidents of snakebites relative the demography and socioeconomy of the communities, anatomical distribution of snakebites in the victims, and seasonal distribution of the snakebites events). We found a total of 160 species, 5.561 individual registers, of amphibians and Squamata reptiles in the region of the lower Purus River. Amphibians were represented by 75 species and 11 families of Anura and one family of Gymnophiona. Squamata reptilians were represented by 85 species and nine families of lizards (31 species) and eight families of snakes (54 species). The total number of species was represented by many habitat generalists, species that were found in both types of forests. Were noted new records of anuran amphibians Dendropsophus allenorum and Scinax pedromedinae, species characteristics of the southwest Amazon. The sampling techniques used were effective in representing the greater part of the terrestrial herpetofauna, with arboreal and terrestrial habits, and was possible to describe consistent composition patterns of these groups and community structure in the types of forests sampled. Snakes were the herpetofaunal group least diversity known locally because of the difficulties in detection of these species. A greater species richness and number of families was found in the terra firme forests than in the varzea forests. Fossorial and leaf-litter species were less represented in the varzea forests. However, in these varzea forests we found a greater number of tree frogs (Hylidae) and larger heliothermic lizards (Teiidae). The species composition demonstrated that different groups of communities of amphibians and reptiles occupy the terra firme and varzea forests. The species composition of anurans amphibian and Squamata reptilians varied greatly along the altitudinal gradient. The complementary diversity between the terra firme and varzea forests (Beta-β diversity), is associated with the widespread presence of these landscapes, possibly resulting in the large contribution to the heterogeneity of the herpetofauna of the region of the lower Purus River (Gama-γ diversity). There was a significant association between the composition of amphibians and the spatial distribution of the two forest types. This spatial autocorrelation was not expressed in the reptile communities. This spatial autocorrelation was related to interfluvial regions of the Purus River and the Purus River varzea forests connection of the forests to the Amazonas-Solimões Basin. The secondary forests, in relation to the primary forests of the varzea and terra firme, had lower herpetofaina diversity. Regeneration time of the secondary forests influenced the abundance and species richness of anurans and lizards, especially in the terra firme forests. The incidence of snakebites was related to the work environment of the people involved, and harvesting forest products was the activity in which most victims were bitten. Bothrops atrox was the snake responsible for half of the registered snake bites. Identification of snakes by the local people is limited, often one species has several different local names, and the same name is often used for several different species. Snakebite accidents in the communities in RDS-PP represent events with a high health risk and may be lethal. The unavailability of antivenom in this region, usually more than 24 hours for the victim to receive treatment, is the principal cause for complications or death from snakebite.
Keywords: Herpetofauna; Diversidade Beta-β; Floresta de Terra Firme; Florestas de várzea; Ofidismo; RDS Piagaçu-Purus; Rio Purus